Optimization techniques for underfoot pressure measurement - Alwan, Omar Hussein (2017)
A plantar foot pressure measurement provides important information which can be used as a helpful tool for evaluating patients with foot complaints. Foot plantar pressure systems are devices that are used to measure underfoot pressure. They can be classified into two types: platform systems and insole systems. An insole system is flexible and portable, thereby allowing a wider variety of studies to be carried out with different gait tasks, footwear designs and terrains, while a platform system is fixed and limited to the measurement of underfoot pressure in a static condition, and is usually used for the detection of ulceration. Currently, underfoot pressure ranges have not been effectively established, and there is insufficient information about the minimum and maximum values of underfoot pressure. Likewise, constraints with regard to the implementation of insole systems still persist and are represented by the need to put a spacer on the sensor during measurements, with the problem of sensor parameters changing after the calibration. Therefore, optimization of measurement techniques have been proposed for the implementation of an insole system to measure the underfoot pressure to overcome these drawbacks. This research was approved by the Human Research Ethics Committee of Universiti Putra Malaysia. The research was aimed at measuring the pressure of 15 points under the foot for 12 samples, divided into two groups (male and female). Two techniques were used to implement the insole system for the effective measurement of underfoot pressure, namely a sensor optimization of the output voltage swing, and the setting of